Analisis Kuantitatif Kadar Nitrit dalam Produk Daging Olahan di Wilayah Denpasar Dengan Metode Griess Secara Spektrofotometri - Habibah, Nur; Dhyanaputri, I G.A. Sri; Karta, I Wayan; Dewi, Ni Nyoman Astika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Nitrite is one of important food additive that used as a preservative and curing agent for the meat product. Since the adverse effect of nitrites to the human health has been reported, the government regulated maximum allowable nitrite content in meat product is 125 mg/kg. Hence, continuous monitoring of the existence of nitrite, especially in the meat products are important to conducted. Quantitative analysis of nitrite in the meat product, especially sausage has been described. The spectrophotometric measurement of the nitrite contents was conducted by using Griess method. The absorbance of both standard solution and sample carried after 30 minutes at the maximum wavelength 520 nm. A linier calibration curve was obtained in the range of 0.1-0.5 ppm, with the R2 value is 0.997. Subsequently, the method was applied to determine the nitrit contents in sausage samples. The spectrophotometric determination showed there were 6 samples have nitrite contents more than maximum allowable nitrite content in the meat product.